Unraveling the Serum Metabolomic Profile of Post-partum Depression - Papadopoulou, Zoe; Vlaikou, Angeliki-Maria; Theodoridou, Daniela; Komini, Chrysoula; Chalkiadaki, Georgia; Vafeiadi, Marina; Margetaki, Katerina; Trangas, Theoni; Turck, Chris W.; Syrrou, Maria; Chatzi, Leda; Filiou, Michaela D. (Frontiers in Neuroscience, 2019)
Post-partum depression (PPD) is a severe psychiatric disorder affecting ~15% of young mothers. Early life stressful conditions in periconceptual, fetal and early infant periods or exposure to maternal psychiatric disorders, have been linked to adverse child outcomes interfering with physiological, cognitive and emotional development. The molecular mechanisms of PPD are not yet fully understood. Unraveling the molecular underpinnings of PPD will allow timely detection and establishment of effective therapeutic approaches. To investigate the underlying molecular correlates of PPD in peripheral material, we compared the serum metabolomes of an in detail characterized group of mothers suffering from PPD and a control group of mothers, all from Heraklion, Crete in Greece. Serum samples were analyzed by a mass spectrometry platform for targeted metabolomics, based on selected reaction monitoring (SRM), which measures the levels of up to 300 metabolites. In the PPD group, we observed increased levels of glutathione-disulfide, adenylosuccinate and ATP, which associate with oxidative stress, nucleotide biosynthesis and energy production pathways. We also followed up the metabolomic findings in a validation cohort of PPD mothers and controls. To the very best of our knowledge, this is the first metabolomic serum analysis in PPD. Our data show that molecular changes related to PPD are detectable in peripheral material, thus paving the way for additional studies in order to shed light on the molecular correlates of PPD.